Answer:
Explanation:
Equation
5y = 3y + 4
combine like terms 3y becomes negative when moved to the left side being that its positive on the right. 4 has no variable so it stands alone on the right side.
-3y + 5y = 4
After adding a low negative to a high positive number. Turns into 2y.
2y = 4
Divide 2 on both sides to remove the number from the variable on the left.
y =
![(4)/(2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/ajcfaep68gnw0egxw6hl7d3jxr8wxg80ba.png)
2 is canceled on the left side which gives the solution for Y.
y = 2